2D Metallic Transition‐Metal Dichalcogenides: Structures, Synthesis, Properties, and Applications. (21st August 2021) - Zhao, Bei; Shen, Dingyi; Zhang, Zucheng; Lu, Ping; Hossain, Mongur; Li, Jia; Li, Bo; Duan, Xidong
Abstract: 2D materials and the associated heterostructures define an ideal material platform for investigating physical and chemical properties, and exhibiting new functional applications in (opto)electronic devices, electrocatalysis, and energy storage. 2D transition metal dichalcogenides (2D TMDs), as a member of the 2D materials family including 2D semiconducting TMDs (s‐TMDs) and 2D metallic/semimetallic TMDs (m‐TMDs) have attracted considerable attention in the scientific community. Over the past decade, the 2D s‐TMDs have been extensively researched and reviewed elsewhere. Because of their distinctive physical properties including intrinsic magnetism, charge‐density‐wave order and superconductivity, and potential applications, such as high‐performance electronic devices, catalysis, and as metal electrode contacts, 2D m‐TMDs have grabbed widespread attention in recent years. However, reviews demonstrating the m‐TMDs systematically and comprehensively have been rarely reported. Here, the recent advances in 2D m‐TMDs in the aspects of their unique structures, synthetic approaches, distinctive physical properties, and functional applications are highlighted. Finally, the current challenges and perspectives are discussed. Abstract : Metallic/semimetallic transition metal dichalcogenides (m‐TMDs) have grabbed widespread attention in recent years due to their exotic physical properties and potential applications in various fields. The state‐of‐the‐art progress in m‐TMDs is reviewed, including electronic and crystal structures, synthetic methods, physical properties, and practical applications. Moreover, views on development, challenges, and future prospects of m‐TMDs are put forward.